Asuhan Kebidanan pada Kegawatdaruratan Maternal: Studi Literatur tentang Efektivitas Intervensi Kebidanan - Marpaung, Sastrika Handayani (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Maternal emergencies are life-threatening conditions during pregnancy, childbirth, and the postpartum period. Prompt and appropriate midwifery intervention can reduce maternal morbidity and mortality. Objective: To analyze the effectiveness of various midwifery interventions in managing maternal emergencies based on a literature review. Methods: This study used a literature review method by reviewing scientific articles published between 2015 and 2025. Searches were conducted through the PubMed, ScienceDirect, Google Scholar, and DOAJ databases using the keywords "maternal emergency," "midwifery care," and "emergency obstetric intervention." Inclusion criteria included studies discussing midwifery interventions in maternal emergencies, published in English or Indonesian, and available in full-text. Results: Of the 25 articles reviewed, midwifery interventions such as postpartum hemorrhage management with active management of the third stage of labor, the use of magnesium sulfate in preeclampsia/eclampsia, fluid resuscitation in shock, and the partograph technique for labor monitoring were proven effective in reducing complications. Rapid response, clinical skills, and coordination with the medical team were key factors for success. Conclusion: Evidence-based midwifery interventions, implemented quickly and in a coordinated manner, play a significant role in reducing maternal morbidity and mortality. Routine training and capacity building for midwives are needed to strengthen the response to maternal emergencies.